University-industry cooperation: A peer-reviewed bibliometric analysis - Pedro Borges; Mário Franco; Amélia Carvalho; Carlos Machado dos Santos; Margarida Rodrigues; Galv\~ao Meirinhos; Rui Silva (Economies, 2022)
University-industry cooperation is associated with the transfer of knowledge and technology. This collaboration is an extremely important field of study for the world's economies, helping companies to become more competitive. The present research aims to explore and analyze the literature related to university-industry cooperation, using a bibliometric analysis as a methodology. This study intends to use an unlike approach to conduct the literature review and map the most relevant research studies, using a rigorous research protocol based on scientific documents published in the Web of Science database, using the keyword 'University-Industry Cooperation'. The 256 articles collected are situated in a time base between 1970 and 2020 and were submitted to content analysis in R Bibliometrix. This systematic literature review revealed that companies are increasingly focusing on cooperation with universities. The research of these publications points to a growing trend in publications of articles with the topic 'University-Industry Cooperation'. From the bibliometric analysis of the global research results, we highlight the most cited authors and the authors' publications over time, and we also highlight the main research topics and countries where studies were conducted. On the other hand, we also highlight the collaboration network between institutions, authors, and countries over time. The University-Industry cooperation is explored here as an added value for advancing scientific knowledge on the relationship between these two important stakeholders, opening the way for future research in this area. With this article, we hope to contribute to the evolution of scientific knowledge in this area, providing future researchers with a detailed radiography overview of the literature related to University-Industry cooperation, contributing to filling an existing gap related to the scarcity of SLR studies that focus on this scientific theme.
Keywords: 330; bibliometric analysis; systematic literature review; university-industry cooperation